Estado nutricional y nivel socioeconómico en niños con enfermedad diarreica aguda de la parroquia rural Yangana del cantón Loja. - Masache Jumbo, Paula Verónica (2019)
Acute diarrheal disease is one of the main causes of morbidity in the population of children under 5 years of age worldwide, especially in developing countries. The high incidence of this is linked to socioeconomic determinants, which produce inequalities between communities affecting their quality of life especially that of children who are affected being the target of diseases such as malnutrition. This cross-sectional, descriptive, and correlational research carried out in the rural parish of Yangana, Loja, in children under 5 years, aimed to analyze the relationship between nutritional status and socioeconomic level in a group of children under 5 years of age diagnosed with acute diarrheal disease. For this, a sample of 85 minors who attended the Health Center with the aforementioned diagnosis was used. Based on the documented information, we proceeded to calculate the body mass index. An econometric instrument was applied to capture the socioeconomic information. The nutritional status indicator (BMI) reveals that 65,9% of children have a adequate nutritional status, while 21,2% and 7,1% have malnutrition and severe malnutrition. In terms of the socioeconomic level, 41,2% belong to a social stratum IV or relative poverty. Finally, to determine the relationship between the variables the Spearman correlation coefficient is used, exhibiting a very low or weak positive correlation (Rho= 0,116) rejecting the statistically null hypothesis given that the coefficient is not significant (p=0,291). Keywords: Nutritional status, socioeconomic level, acute diarrhea.